Endowment Effect Do We Appreciate More Information from Books? - Hadincová, Ludmila (2011)
The main purpose of this thesis is to answer a question, whether an individual appreciates more information originating from physical media than information from virtual media. Respectively, if these two types of media have a different impact on the endowment effect. This effect is conditioned by the individual's physical possession of an object that is provided by physical media, but not allowed by virtual media. The first part of the experiment is based on the comparison of buyer's willingness to pay for information from physical and virtual media (WTP) with seller's willingness to accept payment for the information (WTA). The results from the first part of the experiment did not satisfy the hypothesis about participant's higher valuation of information from physical media. But it was found out that buyers were more willing to pay for the information from physical media suggesting the emergence of quasi-endowment effect. Subjects were reluctant to pay for the electronic version of information. The second part of the experiment is based on comparison of participant's preferences for books in regular and virtual format. It was proved that participants who had an experience only with the book in electronic format were more eager to exchange it for the other book. The opposite effect was documented for participants who had the book in regular format. So, the results from the second part of the experiment provided weak evidence on behalf of the prediction about greater impact of physical media information on the endowment effect. The thesis is further focused on detection of personal characteristic's impacts on the endowment effect. Finally, it was discovered that subjects felt loss aversion of information and that information from books were perceived trustworthier.